2012
DOI: 10.1016/j.jval.2012.08.880
|View full text |Cite
|
Sign up to set email alerts
|

PMD31 Impact of Using a Vessel Sealer System and the Harmonic Scalpel in Hospital Outcomes and Cost of Thyroidectomy Procedures

Abstract: OBJECTIVES:To compare the clinical and cost consequences of Gadoxetic Acidenhanced magnetic resonance imaging (PV-MRI) to extracellular contrast mediaenhanced MRI (ECCM-MRI) and Multidetector Computed Tomography (MD-CT) in patients with suspected hepatocellular carcinoma (HCC) in South Korea and Thailand. METHODS: The clinical pathway of patients with suspected HCC from the initial imaging procedure (PV-MRI, ECCM-MRI or MD-CT) to the confirmed treatment decision was presented in an economic decision-tree model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Although ours is the first study to investigate the clinical outcomes and cost-effectiveness of using the electrothermal bipolar vessel sealing system and ultrasonic shears in oral and oropharyngeal cancer surgery, the same aspects have been studied in the field of thyroid surgery, with conflicting results. Reported benefits include a more efficient utilisation (shorter time) of the operating theatre 2 , 3 , 30 and shorter operating time, 31 consistent with our results. Hallgrimsson et al .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although ours is the first study to investigate the clinical outcomes and cost-effectiveness of using the electrothermal bipolar vessel sealing system and ultrasonic shears in oral and oropharyngeal cancer surgery, the same aspects have been studied in the field of thyroid surgery, with conflicting results. Reported benefits include a more efficient utilisation (shorter time) of the operating theatre 2 , 3 , 30 and shorter operating time, 31 consistent with our results. Hallgrimsson et al .…”
Section: Discussionsupporting
confidence: 87%
“…reported cost savings with the ultrasonic shears compared to the traditional technique, as a result of the significant decrease in operative time (30 per cent), with lower costs for drugs, personnel and operating theatre charges 4 . Da Silva et al ., by contrast, reported that ultrasonic shears and electrothermal bipolar vessel sealing increased the total cost of thyroidectomy procedures, despite the fact that mean operative times decreased by approximately 32 minutes with ultrasonic shears compared to the conventional technique 3 . This finding may be explained by the fact that there was no effect on the length of hospital stay, which we believe to be the most influential parameter in the final cost of any surgical procedure.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Regarding blood loss during thyroidcetomy, some investigators reported significant decrease in blood loss with HS use [5]. Others did not show any difference [6,13,16]. In this study HS showed significant advantages, including less intra-operative blood loss( p= 0.014) and the less use of drains( p-< 0.005).The lesser need for drains and haemostatic agents was also reported by Materzzi G et al [12].…”
Section: Surgical Techniquesupporting
confidence: 71%
“…Some of them considering the indirect money saving like: less hospital stay, less costs for hypocalcaemia management and lower non medical resources [5,12]. However, higher costs when HS is used are reported from other centers and this is mainly due to the cost of the hand piece even without considering the costs related to the generator which is usually provided to hospitals by the manufacturing company [16,18]. We think that the advantages of HS use including shorter operation time, less TH, less blood loss, less use of drains and less hospital stay compensate for the extra costs.…”
Section: Surgical Techniquementioning
confidence: 99%